Graphic design rants and raves bon mots on persuasion, entertainment, education, culture, and practice - Heller, Steven 1950- (Allworth Press, 2016)
"From commercial advertising to government institutions to cultural revolution, from the objects that push design forward to those that seep into the everyday, Graphic Design Rants and Raves is an exploration of how visual design has arrived in the twenty-first century"--From back cover
Includes index
Keywords: Geschichte; Kultur; Grafikdesign; Graphic arts / History; Commercial art / History